One hundred years of solitude, struggle, and violence along the US/Mexico border : an oral history - Thomas, John, 1955- (Cambridge Scholars Publishing, 2017)
This book feature oral histories, mainly of members of the ranching families who have lived in the Mexican State of Sonora and the corresponding territory in the US that stretches from Tijuana on the California border to Agua Prieta on the Arizona border. The elders in those families recall the tales that their grandparents told, providing a century of perspectives on the revolution in economics, culture, and drug trade that the area has witnessed. The book uses the voices of those who have lived through the vicissitudes of border life to paint this cultural upheaval in gripping, personal term.